Gay liberation after May '68 - Hocquenghem, Guy, 1946-1988 (Theory Q., 2022)
"Gay Liberation after May '68 consists of a series of journal articles, communiqués, and manifestos written by Guy Hocquenghem in the years following the May '68 uprising in France, detailing the rise of the militant gay liberation movement alongside the women's movement and other revolutionary organizing. Hocquenghem's second book, this work situates the theories of homosexual desire from Homosexual Desire (1972) in the realm of revolutionary practice. Writing after the apparent failure and eventual selling out of the revolutionary dream of May '68, Hocquenghem persists in a radical vision of the world framed through a queerness that undoes the oppressions of capitalism and empire. The texts compiled here both give an archival glimpse into the issues queer revolutionaries faced at the time and also speak to today's radical queers looking to transform their world"--